Method for testing acid strength and acid production efficiency by using photoetching machine and application
By conducting lithography tests on a lithography machine, using exposure energy data to test the acidic strength and acid production efficiency of photoacid generators, the problem of difficulty in accurate testing in the prior art is solved, and better control of the photoresist performance is achieved.
Patent Information
- Application Number
- CN202510266136.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-24
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to accurately test the acidic intensity of photoacid-producing agents and the acid-producing efficiency of photoacid-producing agents, which makes it difficult to control the impact of photoresist performance, and traditional acid-base titration methods have difficulties in selecting solvents and acid type selection problems.
The photolithography test is carried out using a lithography machine, and the photoacid production acidic intensity and acid production efficiency of photoacid-generating agents are tested through exposure energy data (Eop data), and the test is assisted by existing lithography processes and precision equipment.
Accurate measurement of the acidic strength and acid production efficiency of photoacid generators is achieved, reducing the number of experiments and costs, and improving the scientificity and accuracy of photoresist formulas.
Smart Images

Figure SMS_15 
Figure SMS_20 
Figure SMS_25
Abstract
Description
Technical Field
[0001] The present invention relates to the field of analysis and detection, and in particular to a method and application of testing acid strength and acid production efficiency using a photolithography machine. Background Art
[0002] Photoacid generators are a class of photosensitive compounds that can generate a certain amount and intensity of photoacid under light of a specific wavelength. The acid may appear in the form of a proton acid or a Lewis acid. Photoacid generation is commonly used in industries such as photoresists and photocurable coatings. In photoresists, the acid generated by light can catalyze the reaction of resins, thereby reversing the solubility of the resin and achieving a solubility difference between the exposed area and the non-exposed area; in photocurable coatings, the acid generated by light can initiate cationic polymerization of monomers to achieve photocuring. The efficiency of the above two effects is closely related to the acid strength and acid generation efficiency. The following aspects specifically affect the performance of photoresists: 1) Impact on the photosensitivity of photoresist: Sensitivity: The acid strength of photo-generated acid directly affects the sensitivity of photoresist. The higher the acid strength, the more acid is generated in the photoresist at the same exposure dose, the faster and more complete the chemical reaction is, the higher the sensitivity of the photoresist is, and effective exposure and patterning can be achieved at a lower exposure dose.
[0003] 2) Influence on the chemical structure and reaction of photoresist: Cross-linking and degradation reaction: In positive photoresist, the acid strength of photo-generated acid determines the extent of the degradation reaction of photoresist. When the acid strength is high enough, it can effectively catalyze the shedding of the protective groups on the photoresist molecular chain, making the photoresist more soluble in the developer, thus forming a clear pattern. In negative photoresist, the acid strength of photo-generated acid affects the efficiency of the cross-linking reaction. High-strength acid can promote the formation of more cross-linking points, so that the photoresist forms a cross-linked network after development, and has better anti-etching performance; Reaction rate: Acid strength is one of the key factors affecting the chemical reaction rate of photoresist. Higher acid strength will accelerate the chemical reaction rate in the photoresist, so that the reaction during exposure and post-processing can be completed in a shorter time. It is of great significance to improve the production efficiency of the photolithography process.
[0004] 3) Impact on photoresist resolution and pattern quality: Resolution: The acid strength of photo-generated acid has a direct impact on the resolution of photoresist. During the photolithography process, the higher the acid strength, the more confined the chemical reaction of the photoresist in the exposed area is to the exposed area, and a finer pattern can be formed, thereby improving the resolution of the photoresist; Pattern profile: The acid strength also affects the profile and sidewall verticality of the photoresist pattern. Appropriate acid strength can enable the photoresist to form a clear and regular pattern profile with good sidewall verticality during the development process. If the acid strength is too high or too low, it may cause problems such as deformation of the pattern profile, increased roughness or sidewall tilt, affecting the quality of the photolithography pattern.
[0005] 4) Impact on the stability and process window of photoresist: Stability: The acid strength of photo-generated acid is closely related to the stability of photoresist. Too high acid strength may cause unnecessary chemical reactions in the photoresist during storage or use, reducing the stability and shelf life of the photoresist; Process window: Acid strength affects the size of the photolithography process window. Appropriate acid strength can enable the photoresist to obtain good patterning effects within a wider range of exposure doses and development conditions, that is, it has a larger process window. When the acid strength is inappropriate, the process window of the photoresist will become narrower, and the control requirements for process parameters will be more stringent, increasing the difficulty and cost of the photolithography process.
[0006] Although the acid strength of photoacid and the acid generation efficiency of photoacid generator have the above-mentioned many effects on photoresist, it is difficult to accurately test the acidity or acid generation efficiency of photoacid in the prior art. The method commonly used to test the acid strength is acid-base titration, but this technology has problems such as difficulty in selecting solvents due to solubility problems, difficulty in distinguishing two acids of similar strength, and problem in selecting the type of base used during titration. In addition, the acid-base titration method can only infer the acid content by the amount of base consumed, and cannot accurately calculate the acid strength, nor can it calculate the acid generation efficiency of various types of photoacids.
[0007] Based on the above situation, the existing technology can only tentatively select a suitable photoacid generator through a large number of repeated experiments, and consumes a lot of financial resources and energy in testing the acid strength of the photoacid generated by the photoacid generator and the acid generation efficiency of the photoacid generator; and can only form personal experience that cannot be described or quantified, which is not conducive to the development of scientific theories in related fields. In addition, most photoacid generators are not easily soluble in water, and there are technical problems that need to be solved urgently, such as inaccurate measurements when using traditional acid-base titration. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a method for testing acid strength and acid generation efficiency using a photolithography machine, comprising the following steps: Step 1, preparing a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator (PAG), a quencher, a resin, a leveling agent, and a solvent; Step 2: Performing a photolithography test on the photoresist sample using a photolithography machine according to a photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; Step 3, according to the exposure energy data, obtaining the relative magnitude of the photoacidity intensity generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; Wherein, when the chromophores of the photoacid generator are consistent, the acid intensity of the photoacid generated by the photoacid generator increases as the exposure energy data decreases; When the chromophores of the photoacid generator are different but the photoacid generated is the same, the acid generation efficiency of the photoacid generator increases as the exposure energy data decreases.
[0009] Furthermore, the photoacid generator in step 1 includes one of a sulfonium salt ionic photoacid generator, an iodonium salt ionic photoacid generator, a sulfonyldiazomethane molecular photoacid generator, a sulfonyloxyimide molecular photoacid generator, a polyphenol sulfonate molecular photoacid generator, a nitrobenzyl sulfonate molecular photoacid generator, a glyoxime molecular photoacid generator, and a di-(trichloromethane)-triazine molecular photoacid generator.
[0010] Furthermore, the structural formula of the sulfonium salt ionic photoacid generator is: , wherein the sulfonium salt is a salt of a sulfonium cation; R 11 , R 12 , R 13 Each of the following is independently selected from H, halogen, cyano, hydroxy, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, 1-20 atoms of heterocyclic ring containing oxygen, nitrogen, sulfur, substituted 1-20 atoms of heterocyclic ring containing oxygen, nitrogen, sulfur, aryl, condensed ring aryl, heteroaryl, substituted aryl, substituted condensed ring aryl, substituted heteroaryl, and alkoxy; Z - is an anion including but not limited to sulfonate, benzenesulfonate, hexafluoroantimonate, pentafluorophosphate, sulfonimide, imide, or Z - It is an anion which is fully or partially fluorinated.
[0011] Furthermore, R 11 , R 12 , R 13 It can also be a group that forms a ring with each other or is connected to any polymer or is connected to another sulfonium salt type ionic photoacid generator.
[0012] Furthermore, the sulfur cations in the sulfonium salt ionic photoacid generator include but are not limited to: (4-methylphenyl)diphenylsulfonium, (4-methoxyphenyl)diphenylsulfonium, tris(4-methoxyphenyl)sulfonium, (4-tert-butylphenyl)diphenylsulfonium, (4-tert-butoxyphenyl)diphenylsulfonium, bis(4-tert-butoxyphenyl)phenylsulfonium, tris(4-tert-butylphenyl)sulfonium, tris(4-tert-butoxyphenyl)sulfonium, tris(4-methylphenyl)sulfonium, (4-methoxy-3,5-dimethylphenyl)dimethylsulfonium, (3-tert-butoxyphenyl)diphenylsulfonium, bis(3-tert-butoxyphenyl)phenylsulfonium, tris(3-tert-butoxyphenyl)sulfonium, (3,4-di-tert-butoxyphenyl)diphenylsulfonium, bis(3,4-di-tert-butoxyphenyl)phenylsulfonium, tris(3,4-di-tert-butoxyphenyl)sulfonium, (4 The present invention is one of (4-tert-butoxyphenyl)diphenylsulfonium, (4-cyclohexylphenyl)diphenylsulfonium, bis(p-phenylene)bis(diphenylsulfonium), diphenyl(4-thiophenoxyphenyl)sulfonium, diphenyl(4-thiophenylphenyl)sulfonium, diphenyl(8-thiophenylbiphenyl)sulfonium, (4-tert-butoxycarbonylmethoxyphenyl)diphenylsulfonium, tris(4-tert-butoxycarbonylmethoxyphenyl)sulfonium, (4-tert-butoxyphenyl)bis(4-dimethylaminophenyl)sulfonium, tris(4-dimethylaminophenyl)sulfonium, 2-naphthyldiphenylsulfonium, dimethyl(2-naphthyl)sulfonium, 4-hydroxyphenyldimethylsulfonium, 4-methoxyphenyldimethylsulfonium, trimethylsulfonium, 2-oxocyclohexylcyclohexylmethylsulfonium, trinaphthylsulfonium and tribenzylsulfonium.
[0013] Furthermore, Z in the sulfonium salt ionic photoacid generator is - Anions include, but are not limited to, trifluoromethanesulfonate, nonafluorobutanesulfonate, heptadecafluorooctanesulfonate, 2,2,2-trifluoroethanesulfonate, pentafluorobenzenesulfonate, 4-(trifluoromethyl)benzenesulfonate, 4-fluorobenzenesulfonate, toluenesulfonate, benzenesulfonate, 4-(4-toluenesulfonyloxy)benzenesulfonate, naphthalenesulfonate, camphorsulfonate, octanesulfonate, dodecylbenzenesulfonate, butanesulfonate, and methanesulfonate. one; or one of bis(perfluoromethanesulfonyl)imide, bis(perfluoroethanesulfonyl)imide, bis(perfluorobutanesulfonyl)imide, bis(perfluorobutanesulfonyloxy)imide, bis[perfluoro(2-ethoxyethane)sulfonyl]imide, N,N-hexafluoropropane-1,3-disulfonyl imide; or tris[(trifluoromethyl)sulfonyl]methane, tris[(perfluorobutyl)sulfonyl]methane anion.
[0014] Furthermore, the structural formula of the iodonium salt-based ionic photoacid generator is: , wherein the iodonium salt is a salt of an iodine cation; R 21 , R 22Each of them is independently H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group.
[0015] Furthermore, the iodine cations in the iodonium salt-based ionic photoacid generator include but are not limited to: Diphenyliodonium, (4-methoxyphenyl)-phenyliodonium, bis(4-methoxyphenyl)iodonium, (4-tert-butylphenyl)-phenyliodonium, (4-tert-butoxyphenyl)phenyliodonium, bis(4-tert-butoxyphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(4-tert-butoxyphenyl)iodonium, bis(4-methylphenyl)iodonium, bis(4-methoxy-3,5 1-dimethylphenyl)dimethyl iodide, (4-methoxy-3,5-dimethylphenyl)methyl iodide, dimethyl iodide, (3-tert-butoxyphenyl)phenyl iodide, bis(3-tert-butoxyphenyl)iodide, bis(3-tert-butoxyphenyl)iodide, (3,4-di-tert-butoxyphenyl)phenyl iodide, bis(3,4-di-tert-butoxyphenyl)iodide, bis(3,4-di-tert-butoxyphenyl)iodide iodonium, (4-phenoxyphenyl)phenyl iodonium, (4-cyclohexylphenyl)phenyl iodonium, bis(p-phenylene)bis(diphenyl iodonium), diphenyl(4-thiophenoxyphenyl)iodonium, diphenyl(4-thiophenylphenyl)iodonium, diphenyl(8-thiophenylbiphenyl)iodonium, (4-tert-butoxycarbonyl)-methoxyphenyl-iodonium, bis(4-tert-butoxycarbonyl)-methoxyphenyl-iodonium, one of (4-tert-butoxyphenyl)-(4-dimethylaminophenyl) iodonium, (4-tert-butoxyphenyl)-(4-dimethylaminophenyl) iodonium, bis(4-dimethylaminophenyl) iodonium, 2-naphthylphenyl iodonium, methyl(2-naphthyl) iodonium, 4-hydroxyphenylmethyl iodonium, 4-methoxyphenylmethyl iodonium, bismethyl iodonium, 2-oxocyclohexylcyclohexylmethyl iodonium, dinaphthyl iodonium and bisbenzyl iodonium; X - is an anion including but not limited to sulfonate, benzenesulfonate, hexafluoroantimonate, pentafluorophosphate, sulfonimide, imide, amide, or X - It is an organic anion which is fully or partially fluorinated.
[0016] Furthermore, the X in the iodonium salt ionic photoacid generator is -Anions include, but are not limited to, trifluoromethanesulfonate, nonafluorobutanesulfonate, heptadecafluorooctanesulfonate, 2,2,2-trifluoroethanesulfonate, pentafluorobenzenesulfonate, 4-(trifluoromethyl)benzenesulfonate, 4-fluorobenzenesulfonate, toluenesulfonate, benzenesulfonate, 4-(4-toluenesulfonyloxy)benzenesulfonate, naphthalenesulfonate, camphorsulfonate, octanesulfonate, dodecylbenzenesulfonate, butanesulfonate, methanesulfonate. one; or one of bis(perfluoromethanesulfonyl)imide, bis(perfluoroethanesulfonyl)imide, bis(perfluorobutanesulfonyl)imide, bis(perfluorobutanesulfonyloxy)imide, bis[perfluoro(2-ethoxyethane)sulfonyl]imide, N,N-hexafluoropropane-1,3-disulfonyl imide; or tris[(trifluoromethyl)sulfonyl]methane, tris[(perfluorobutyl)sulfonyl]methane anion.
[0017] Furthermore, R 21 , R 22 It can also be a group that forms a ring with each other or is connected to any polymer or is connected to another iodonium salt type ionic photoacid generator.
[0018] Furthermore, the structural formula of the sulfonyldiazomethane molecular photoacid generator is: , where R 31 , R 32 Each of them is independently H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group.
[0019] Furthermore, R 31 , R 32 It can also be a group that forms a ring with each other or is connected to any polymer or is connected to another sulfonyldiazomethane type molecular type photoacid generator.
[0020] Furthermore, the sulfonyldiazomethane molecular photoacid generator includes but is not limited to bis(ethylsulfonyl)diazomethane, bis(1-methylpropylsulfonyl)diazomethane, bis(2-methylpropylsulfonyl)diazomethane, bis(1,1-dimethylethylsulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(perfluoroisopropylsulfonyl)diazomethane, bis(phenylsulfonyl)diazomethane, bis(4-methylphenylsulfonyl)diazomethane, Diazomethane, bis(2,4-dimethylphenylformyl)diazomethane, bis(2-naphthylsulfonyl)diazomethane, 4-methylphenylsulfonylbenzoyldiazomethane, tert-butylcarbonyl-4-methylphenylsulfonyldiazomethane, 2-naphthylsulfonylbenzoyldiazomethane, 4-methylphenylsulfonyl-2-naphthoyldiazomethane, methylsulfonylbenzoyldiazomethane, tert-butyloxycarbonyl-4-methylphenylsulfonyldiazomethane.
[0021] Furthermore, the structural formula of the sulfonyloxyimide molecular photoacid generator is: , wherein the sulfonyloxyimide molecular photoacid generator is composed of a sulfonate group and an imide; R 41 , R 42 , R 43 Each of them is independently H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group.
[0022] Furthermore, R 41 , R 42 , R 43 They can also be groups that are cyclic or connected to any polymer.
[0023] Further, the sulfonate group includes but is not limited to: one of trifluoromethanesulfonate, nonafluorobutanesulfonate, heptadecafluorooctanesulfonate, 2,2,2-trifluoroethanesulfonate, pentafluorobenzenesulfonate, 4-(trifluoromethyl)benzenesulfonate, 4-fluorobenzenesulfonate, toluenesulfonate, benzenesulfonate, 4-(4-toluenesulfonyloxy)benzenesulfonate, naphthalenesulfonate, camphorsulfonate, octanesulfonate, dodecylbenzenesulfonate, butanesulfonate, and methanesulfonate.
[0024] Further, the imide includes but is not limited to: succinimide, naphthalimide, phthalimide, cyclohexyldicarboximide, 5-norbornene 2,3-dicarboximide and 7-oxabicyclo[2.2.1]-5-heptene-2,3-dicarboximide, bis(perfluoromethanesulfonyl)imide, bis(perfluoroethanesulfonyl)imide, bis(perfluorobutanesulfonyl)imide, bis(perfluorobutanesulfonyloxy)imide, bis[perfluoro(2-ethoxyethane)sulfonyl]imide, one of N,N-hexafluoropropane-1,3-disulfonyl imide.
[0025] Furthermore, the structural formula of the polyphenol sulfonate molecular photoacid generator is: The structure of the polyphenol sulfonate molecular photoacid generator includes a polyphenol structure and a sulfonate group, which together form a sulfonate group. The structure of the polyphenol sulfonate molecular photoacid generator contains more than one sulfonate group and more than one R 51 substituent, so each R 51 , R 52 Each of them is independently H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group.
[0026] Furthermore, R 51 , R 52 It can also be a group connected to any polymer or to another polyphenol sulfonate molecule-type photoacid generator.
[0027] Furthermore, the polyphenol structure includes but is not limited to: catechol, hydroquinone, resorcinol, trisphenol, 1,2,4-trisphenol, meta-trisphenol, biphenol, bisphenol A, trisphenol A, catechol, (2R,3S)-3,3',4',5,7-pentahydroxyflavan-3-ol, (2R,3S)-2-(3,4-dihydroxyphenyl)-3,4-dihydroxy-5-[(2S,3R)-2,3-dihydroxy-3-(4-hydroxyphenyl)propyl]benzoic acid, (2R,3R)-3,3',4',5,7-pentahydroxyflavan -3-ol, (2R,3S)-2-(3,4-dihydroxyphenyl)-3,4,5-trihydroxy-[(2S,3R)-2,3-dihydroxy-3-(4-hydroxyphenyl)propyl]benzoic acid, 2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-2H-chromone, 3,5,4'-trihydroxy-trans-stilbene, 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione, 4,4',5,7-tetrahydroxybisbenzo[b,d]pyran-6,6'-dicarboxylic acid.
[0028] Further, the sulfonate group includes but is not limited to: one of trifluoromethanesulfonate, nonafluorobutanesulfonate, heptadecafluorooctanesulfonate, 2,2,2-trifluoroethanesulfonate, pentafluorobenzenesulfonate, 4-(trifluoromethyl)benzenesulfonate, 4-fluorobenzenesulfonate, toluenesulfonate, benzenesulfonate, 4-(4-toluenesulfonyloxy)benzenesulfonate, naphthalenesulfonate, camphorsulfonate, octanesulfonate, dodecylbenzenesulfonate, butanesulfonate and methanesulfonate.
[0029] Furthermore, the structural formula of the nitrobenzyl sulfonate type molecular photoacid generator is: , where R 61 , R 62 , R 63 Each of the following is independently selected from H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group; and the benzene ring contains at least one nitro group.
[0030] Furthermore, R 61 , R 62 , R 63 It can also be a group that forms a ring with each other or is connected to any polymer or is connected to another nitrobenzyl sulfonate type molecular type photoacid generator.
[0031] Further, the nitrobenzyl sulfonate type molecular photoacid generator includes but is not limited to: one of 2,4-dinitrobenzyl sulfonate, 2-nitrobenzyl sulfonate, and 2, 6-dinitrobenzyl sulfonate; the sulfonate (salt) in the nitrobenzyl sulfonate type molecular photoacid generator includes but is not limited to: one of trifluoromethanesulfonate, nonafluorobutanesulfonate, heptadecafluorooctanesulfonate, 2,2,2-trifluoroethanesulfonate, pentafluorobenzenesulfonate, 4-trifluoromethylbenzenesulfonate, 4-fluorobenzenesulfonate, toluenesulfonate, benzenesulfonate, naphthalenesulfonate, camphorsulfonate, octanesulfonate, dodecylbenzenesulfonate, butanesulfonate, and methanesulfonate.
[0032] Furthermore, the structural formula of the glyoxime-based molecular photoacid generator is: , where R 71 , R 72 , R 73 , R 74 Each of them is independently H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, a heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, a substituted heterocycle containing 1-20 atoms of oxygen, nitrogen and sulfur, an aryl, a condensed ring aryl, a heteroaryl, a substituted aryl, a substituted condensed ring aryl, a substituted heteroaryl, and an alkoxy group.
[0033] Furthermore, R 71 , R 72 , R 73 , R 74 It can also be a group that forms a ring with each other or is connected to any polymer or is connected to another glyoxime type molecular type photoacid generator.
[0034] Further, the glyoxime-based molecular photoacid generator includes but is not limited to: bis-O-(p-toluenesulfonyl)-α-dimethylglyoxime, bis-O-(p-toluenesulfonyl)-α-diphenylglyoxime, bis-O-(p-toluenesulfonyl)-α-dicyclohexylglyoxime, bis-O-(p-toluenesulfonyl)-2,3-pentanedioneglyoxime, bis-O-(p-toluenesulfonyl)-2-methyl-3,4-pentanedioneglyoxime, bis-O-(n-butylsulfonyl)-α-dimethylglyoxime, bis-O-(n-butylsulfonyl)-α-diphenylglyoxime, bis-O-(n-butylsulfonyl)-α-dicyclohexylglyoxime, bis-O-(n-butylsulfonyl)-2,3-pentanedioneglyoxime, bis-O-(n-butylsulfonyl)- )-2-methyl-3,4-pentanedione glyoxime, bis-O-(methylsulfonyl)-α-dimethylglyoxime, bis-O-(trifluoromethanesulfonyl)-α-dimethylglyoxime, bis-O-(1,1,1-(trifluoroethanesulfonyl)-α-dimethylglyoxime, bis-O-(tert-butanesulfonyl)-α-dimethylglyoxime, bis-O-(perfluorooctanesulfonyl)-α-dimethylglyoxime, bis-O-(cyclohexylsulfonyl) One of α-dimethylglyoxime, bis-O-(benzenesulfonyl)-α-dimethylglyoxime, bis-O-(p-fluorobenzenesulfonyl)-α-dimethylglyoxime, bis-O-(p-tert-butylbenzenesulfonyl)-α-dimethylglyoxime, bis-O-(xylenesulfonyl)-α-dimethylglyoxime and bis-O-(camphorsulfonyl)-α-dimethylglyoxime.
[0035] Furthermore, the structural formula of the di-(trichloromethane)-triazine molecular photoacid generator is: , where R 81 It is one of H, halogen, cyano, hydroxyl, amino, nitro, 1-20 C alkyl, cycloalkyl, spiro, bridged ring, condensed ring, substituted alkyl, substituted cycloalkyl, substituted spiro, substituted bridged ring, substituted condensed ring, heterocyclic ring containing 1-20 atoms of oxygen, nitrogen and sulfur, substituted heterocyclic ring containing 1-20 atoms of oxygen, nitrogen and sulfur, aryl, condensed ring aryl, heteroaryl, substituted aryl, substituted condensed ring aryl, substituted heteroaryl, and alkoxy.
[0036] Furthermore, R 81 It can also be a group attached to any polymer or to another di-(trichloromethane)-triazine type molecular type photoacid generator.
[0037] Furthermore, the quencher in step 1 includes one or more of pyridine compounds, tertiary alkylamines, alicyclic amines, trialkanol tertiary amines, tetraalkylammonium hydroxides, and vinylpyridine polymers.
[0038] Furthermore, the pyridine compound includes, but is not limited to, one or more of pyridine, picoline, dimethylpyridine, and α,α,α-terpyridine.
[0039] Furthermore, the tertiary alkylamine includes but is not limited to one or more of triethylamine, tri-n-butylamine, tri-n-octylamine, dioctylmethylamine, dicyclohexylmethylamine, dimethyldodecylamine, dimethylhexadecylamine, tribenzylamine, and tri[2-(2-methoxyethoxy)ethyl]amine.
[0040] Furthermore, the alicyclic amine includes but is not limited to one or more of N-methylpyrrolidine, N-methylpiperidine, and 1,4-diaminobicyclo[2,2,2]octane.
[0041] Furthermore, the trialkanol tertiary amine includes but is not limited to one or more of triethanolamine and triisopropanolamine.
[0042] Furthermore, the tetraalkylammonium hydroxide includes, but is not limited to, one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide (TPAH), and tetra-n-butylammonium hydroxide.
[0043] Furthermore, the vinylpyridine polymer includes but is not limited to one or more of polyvinylpyridine, poly(vinylpyridine / methyl methacrylate), and the like.
[0044] Furthermore, the quencher is preferably one or more of α,α,α-terpyridine, dioctylmethylammonium, tri-n-octylamine, dicyclohexylmethylammonium, dimethyldodecylammonium, dimethylhexadecylammonium, 1,4-diazabicyclo[2,2,2], octanylammonium, and tetrapropylammonium hydroxide.
[0045] Furthermore, the resin in step 1 is a copolymer or a homopolymer, with a molecular weight Mw of 3000-100,000 and a molecular weight distribution index PDI value of 1.02-3.
[0046] Furthermore, the monomer of the homopolymer is one of a styrene monomer, an acrylate monomer, a vinyl ether monomer, and a vinyl alcohol ester monomer.
[0047] Furthermore, the molar ratio of each monomer in the copolymer to the total monomers is greater than 0% and less than or equal to 99%.
[0048] Furthermore, the preferred structural formula of the resin is: , , , , , One or more of the following; among which, m 11 、n 12 、r13 The quantity ratio is 60 / 20 / 20, or 65 / 20 / 15; n 22 The quantity in the corresponding structure accounts for one of 15%, 20%, or 25%; n 32 The quantity in the corresponding structure accounts for one of 20%, 30%, or 35%; n 42 The quantity in the corresponding structure accounts for one of 20%, 30%, or 35%; n 52 The quantity in the corresponding structure accounts for one of 20%, 30%, or 35%; n 62 The quantity in the corresponding structure accounts for one of 20%, 30%, or 35%.
[0049] Further, the copolymer includes but is not limited to poly(p-hydroxystyrene / styrene / tert-butyl acrylate), poly(p-hydroxystyrene / styrene / tert-amyl acrylate), poly(p-hydroxystyrene / styrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / styrene / tetrahydropyranyl acrylate), poly(p-hydroxystyrene / styrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / styrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / styrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / styrene / triphenylmethyl acrylate), poly(p-hydroxystyrene / styrene / 1,1-diphenylethyl acrylate), poly(p-hydroxystyrene / styrene / 1,1-diphenylethyl acrylate), poly(p-hydroxystyrene acrylate), poly(p-hydroxystyrene / styrene / 2-phenyl-2-propyl acrylate), poly(p-hydroxy-a-methylstyrene / styrene / tert-butyl acrylate), poly(p-hydroxy-a-methylstyrene / styrene / tert-amyl acrylate), poly(p-hydroxystyrene / styrene / tert-butyl methacrylate), poly(p-hydroxystyrene / styrene / tert-amyl methacrylate), poly(p-hydroxystyrene / styrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / styrene / tetrahydropyranyl methacrylate), poly(p-hydroxystyrene / styrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / styrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / styrene / methyl acrylate), poly(p-hydroxystyrene / styrene / triphenylmethyl methacrylate), poly(p-hydroxystyrene / styrene / 1,1-diphenylethyl methacrylate), poly(p-hydroxystyrene / ethylene / 2-phenyl-2-propyl methacrylate), poly(p-hydroxy-a-methylstyrene / styrene / tert-butyl methacrylate), poly(p-hydroxy-a-methylstyrene / styrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / m-methylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / tert-butyl methacrylate). acrylate), poly(p-hydroxystyrene / p-methylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / m-methylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / tetrahydropyranyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / m-methylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / m-methylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate),Poly(p-hydroxystyrene / m-methylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / triphenylmethyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / 1,1-diphenylethyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / 2-phenyl-2-propyl acrylate), poly(p-hydroxy-a-methylstyrene / p-methylstyrene / tert-butyl acrylate), poly(p-hydroxy-a-methylstyrene / p-methylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-methylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / tetrahydropyroxyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / 2-methyl-2-adamantyl methacrylate ester), poly(p-hydroxystyrene / p-methylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / m-methylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / triphenylmethyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / 1,1-diphenylethyl methacrylate), poly(p-hydroxystyrene / p-methylstyrene / 2-phenyl-2-propyl methacrylate), poly(p-hydroxy-a-methylstyrene / p-methylstyrene / tert-butyl methacrylate), poly(p-hydroxy-a-methylstyrene / p-methylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-ethylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxy-q-methylstyrene / p-ethylstyrene / tert-pentyl acrylate), poly(p-hydroxy-α-methylstyrene / p-ethylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-ethylstyrene / tert-butyl methacrylate),Poly(p-hydroxystyrene / p-ethylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-ethylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-ethylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-ethylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-ethylstyrene / 4-methyl-2-oxo-4-tetrapyrrolidone methacrylate), poly(p-hydroxy-α-methylstyrene / p-ethylstyrene / tert-butyl methacrylate), poly(p-hydroxy-α-methylstyrene / p-ethylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / tert-butyl acrylate) , poly(p-hydroxystyrene / p-n-propylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-n-propylstyrene 1-adamantyl acrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxy-α-methylstyrene / p-n-propylstyrene / tert-butyl acrylate), poly(p-hydroxy-α-methylstyrene / p-n-propylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-n-propylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-n-propylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxy-a-methylstyrene / p-n-propylstyrene / tert-butyl methacrylate), poly(p-hydroxy-q-methylstyrene / p-n-propylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-isopropylstyrene / acrylic acid tert-butyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxy-a-methylstyrene p-isopropylstyrene / tert-butyl acrylate), poly(p-hydroxy-a-methylstyrene / p-propylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-isopropylstyrene / tert-butyl methacrylate),Poly(p-hydroxystyrene / p-isopropylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-isopropylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxy-0-methylstyrene / p-isopropylstyrene / tert-butyl methacrylate), poly(p-hydroxy-a-methylstyrene / p-isopropylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-n-butylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / p-butylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / p-butylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-butylstyrene / tert-butyl methacrylate), poly (p-hydroxystyrene / p-n-butylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-n-butylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-n-butylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-n-butylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-n-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / p-isobutylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / p-isobutylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-isobutylstyrene / 1-methylcyclohexyl acrylate), poly( p-Hydroxystyrene / p-isobutylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-isobutylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-isobutylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / p-isobutylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / p-isobutylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-isobutylstyrene / methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-isobutylstyrene / adamantyl methacrylate), poly(p-hydroxystyrene / p-isobutylstyrene / 2-methyl-2-adamantyl methacrylate),Poly(p-hydroxystyrene / p-isobutylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / tert-butyl methacrylate), poly (p-hydroxystyrene / p-sec-butylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-sec-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / tert-butyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / tert-amyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 1-methylcyclohexyl acrylate), poly(p-hydroxystyrene ethylene / p-tert-butylstyrene / 1-adamantyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 2-methyl-2-adamantyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / triphenylmethyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 1,1-diphenylethyl acrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 2-phenyl-2-propyl acrylate), poly(p-hydroxy-q-methylstyrene / p-tert-butylstyrene / tert-butyl acrylate), poly(p-hydroxy-a-methylstyrene / p-tert-butylstyrene / tert-amyl acrylate), poly(p-hydroxy methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / tert-butyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / tert-amyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 1-methylcyclohexyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 1-adamantyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 2-methyl-2-adamantyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / 4-methyl-2-oxo-4-tetrapyranyl methacrylate), poly(p-hydroxystyrene / p-tert-butylstyrene / triphenylmethyl methacrylate, poly(p-hydroxystyrene / p-tert-butylstyrene / 1,1-diphenylethyl methacrylate),One or more of poly(p-hydroxystyrene-p-tert-butylstyrene / 2-phenyl-2-propyl methacrylate), poly(p-hydroxy-a-methylstyrene / p-tert-butylstyrene / tert-butyl methacrylate), and poly(p-hydroxy-a-methylstyrene / p-tert-butylstyrene / tert-amyl methacrylate).
[0050] Furthermore, the leveling agent is a surfactant.
[0051] Furthermore, the surfactant contains a silicon-containing surfactant or a fluorine-containing surfactant.
[0052] Furthermore, the mass content of silicon in the silicon-containing surfactant is 10-50%.
[0053] Furthermore, the mass content of fluorine element in the fluorine-containing surfactant is 20-80%.
[0054] Furthermore, the solvent in step 1 is one or more of a carboxylic acid ester solvent, a ketone solvent, an ether solvent, and a cyclic amide solvent.
[0055] Furthermore, the carboxylate solvent includes but is not limited to: one or more of cellulose acetate methyl, cellulose acetate ethyl, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methyl lactate, ethyl lactate, propyl lactate, 2-ethoxyethyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, and ethyl 3-ethoxypropionate.
[0056] Furthermore, the ketones include but are not limited to one or more of cyclohexanone, methyl ethyl ketone, and 2-heptanone.
[0057] Furthermore, the ether solvent includes, but is not limited to, one or more of propylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, and ethylene glycol monoisopropyl ether.
[0058] Furthermore, the ether solvent also includes a cyclic ether solvent.
[0059] Furthermore, the cyclic ether solvent includes but is not limited to 1,4-dioxane.
[0060] Furthermore, the cyclic amide solvent includes but is not limited to N-methyl-2-pyrrolidone.
[0061] Furthermore, the solvent is preferably one or more of propylene glycol monomethyl ether, cyclohexanone, propylene glycol monomethyl ether acetate, ethyl lactate, ethyl 3-ethoxypropionate, and diethylene glycol monomethyl ether.
[0062] Furthermore, when testing the intensity of the photoacid generated by the photoacid generator, the chromophores in each photoacid generator in the same parallel group are controlled to be exactly the same; the smaller the exposure energy data (Eop data), the stronger the intensity of the photoacid generated by the photoacid generator.
[0063] Furthermore, when testing the acid generation efficiency of the photoacid generator, the structure of the photoacid generated by each photoacid generator in the same parallel group is controlled to be the same, and only the chromophore groups in the photoacid generator are different; when the exposure energy data (Eop data) is smaller, the acid generation efficiency of the photoacid generator is stronger.
[0064] Furthermore, in terms of weight percentage, the proportion of each component in the photoresist formula is: photoacid generator: 0.001-0.3%; quencher: 0.01-0.5%; resin: 1-50%; leveling agent: 0.002%; solvent: 50-90%, the total being 100%.
[0065] Furthermore, after the photoresist sample prepared in step 1 is fully dissolved, it is filtered twice using a 0.1 μm organic membrane to remove tiny particles and dust impurities in the photoresist sample to ensure the purity of the photoresist sample; to ensure accuracy, the filtered formula needs to be stored in a clean bottle for future use.
[0066] Furthermore, the equipment used in the photolithography process includes: a coating and developing machine, a photolithography machine, and a FEB length measuring instrument.
[0067] Furthermore, the model of the coating and developing machine includes but is not limited to one of CLEANTRACK ACT8, ACT12, LITHIUS, LITHIUS Pro, LITHIUS Pro V, LITHIUS Pro Z, and LITHIUS Proap. produced by Tokyo Electron (TEL) of Japan.
[0068] Furthermore, the lithography machine includes but is not limited to a KrF lithography machine, an ArF lithography machine, or an EUV lithography machine.
[0069] Furthermore, the lithography machine includes but is not limited to one of the lithography machines of model 860, model 870, and model 1060 in the TWINSCAN series of ASML; or models NSR-1755Ex8A, NSR-2005Ex10B, NSR-2005Ex8A, NSR-2205Ex12B, NSR-2205Ex14C, NSR-SF200, NSR-S201A, NSR-S202A, NSR-S203A, NSR-S203B, NSR-S204B, NSR-S205C, NSR-S206D, One of NSR-S207D, NSR-S208D, NSR-S210D, NSR-S220D; or one of Canon's models: 3000EX1, 3000EX3, 3000EX3L, 3000EX4, 3000EX5, 3000EX6, 3030EX6, 4000ES1, 5000ES2, 5000ES3, 5000ES4, 6300ES6a, 6300ESW.
[0070] Furthermore, the FEB length measuring instrument includes but is not limited to one of the models CD-SEMS9380, CD-SEM CG4000, CD-SEM CG5100, and CD-SEM CG6300 produced by Hitachi High-Tech Corporation.
[0071] An application of the above method for testing acid strength and acid generation efficiency using a photolithography machine, the method is used to test the relative size of the photoacid strength generated by a photoacid generator and / or the acid generation efficiency of the photoacid generator.
[0072] A database includes test results after testing using the above method for testing acid strength and acid generation efficiency using a photolithography machine.
[0073] The beneficial effects of the present invention are: 1. The present invention is based on the fact that in the prior art, a suitable photoacid generator can only be selected tentatively through a large number of repeated experiments, and a large amount of financial resources and energy are consumed in testing the acid strength of the photoacid generated by the photoacid generator and the acid generation efficiency of the photoacid generator; and only personal experience that cannot be described or quantified is formed, which is not conducive to the development of scientific theories in related fields. In addition, most photoacid generators are not easily soluble in water, and there are technical problems such as inaccurate determination when using traditional acid-base titration. A method for testing the acid strength and acid generation efficiency using a photolithography machine is creatively proposed. With the assistance of an existing photolithography machine and its supporting precision equipment, the relative size of the acid strength of the photoacid generated by the photoacid generator and the acid generation efficiency of the photoacid generator are tested and compared through a known and mature photolithography process; 2. The data obtained by the test of the present invention is used to form a database to assist the theoretical research of organic chemistry, analytical chemistry, photochemistry and other disciplines in a targeted manner; at the same time, it can also provide accurate ideas for the development of photoresist formulas, save scientific research funds, save scientific research time, and improve scientific research efficiency. DETAILED DESCRIPTION
[0074] Embodiment 1-5 is a method for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine; Example 6-9 is a method for testing the relative size of the acid generation efficiency of a photoacid generator using a photolithography machine.
[0075] Example 1 This embodiment provides a method for testing the relative strength of the photoacid generated by a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 1: Table 1 Photoresist formulas for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine
[0076] Among them, the structural formula of PAG-1-1 is: , the structural formula of PAG-1-2 is: , the structural formula of PAG-1-3 is: ; Step 2, perform a photolithography test on the photoresist sample using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃ 60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃ 60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃ 90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; in this embodiment, the exposure energy data (Eop data) of the corresponding formulas of PAG-1-1, PAG-1-2, and PAG-1-3 are 46mj, 33mj, and 25mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and the chromophores of the photoacid generators in the formulas are the same, and only the photoacid structures are different, so the relative size of the acid intensity is explained: .
[0077] Example 2 This embodiment provides a method for testing the relative strength of the photoacid generated by a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 2: Table 2 Photoresist formulas for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine
[0078] Among them, the structural formula of PAG-2-1 is: , the structural formula of PAG-2-2 is: , the structural formula of PAG-2-3 is: ; Step 2, perform a photolithography test on the photoresist sample using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃ 60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃ 60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃ 90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid strength of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; the exposure energy data of the corresponding formulas of PAG-2-1, PAG-2-2, and PAG-2-3 are 42mj, 28mj, and 18mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and the chromophores of the photoacid generators in the formulas are the same, and only the photoacid structure is different, indicating the relative size of the acid strength: The difference between this embodiment and embodiment 1 is that only the chromophore of the photoacid generator is different, but the acid strength results of the photogenerated acid are consistent, thus proving that the testing method of the present invention is effective.
[0079] Example 3 This embodiment provides a method for testing the relative strength of the photoacid generated by a photoacid generator using a photolithography machine, comprising the following steps: Step 1, preparing a photoresist sample according to a photoresist formula; the photoresist formula comprises a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is detailed in Table 3: Table 3 Photoresist formulas for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine
[0080] Among them, the structural formula of PAG-3-1 is: , the structural formula of PAG-3-2 is: , the structural formula of PAG-3-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; in this embodiment, the exposure energy data (Eop data) of the corresponding formulas of PAG-3-1, PAG-3-2, and PAG-3-3 are 40mj, 50mj, and 35mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and the chromophores of the photoacid generators in the formulas are the same, and only the photoacid structures are different, indicating the relative size of the acid intensity: .
[0081] Example 4 This embodiment provides a method for testing the relative strength of the photoacid generated by a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 4: Table 4 Photoresist formulas for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine
[0082] Among them, the structural formula of PAG-4-1 is: , the structural formula of PAG-4-2 is: , the structural formula of PAG-4-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; in this embodiment, the exposure energy data (Eop data) of the corresponding formulas of PAG-4-1, PAG-4-2, and PAG-4-3 are 44mj, 53mj, and 37mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and the chromophores of the photoacid generators in the formulas are the same, and only the photoacid structure is different, which indicates the relative size of the acid intensity: The difference between this embodiment and embodiment 3 is that only the chromophore of the photoacid generator is different, but the acid strength results of the photogenerated acid are consistent, thus proving that the testing method of the present invention is effective.
[0083] Example 5 This embodiment provides a method for testing the relative strength of the photoacid generated by a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 5: Table 5 Photoresist formulas for testing the relative strength of the photoacid generated by the photoacid generator using a photolithography machine
[0084] Among them, the structural formula of PAG-5-1 is: , the structural formula of PAG-5-2 is: , the structural formula of PAG-5-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid strength of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; in this embodiment, the exposure energy data (Eop data) of the corresponding formulas of PAG-5-1, PAG-5-2, and PAG-5-3 are 28mj, 39mj, and 19mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and the chromophores of the photoacid generators in the formulas are the same, and only the photoacid structures are different, which indicates the relative size of the acid strength: The difference between this embodiment and embodiment 3 and embodiment 4 is that in addition to the different chromophores of the photoacid generator, the components of the photoresist formulation are also adjusted, but the acid strength results of the photogenerated acid are consistent, thus proving once again that the testing method of the present invention is effective.
[0085] Example 6 This embodiment provides a method for testing the relative size of the acid generation efficiency of a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 6: Table 6 Relative size of photoresist formulas for testing the acid generation efficiency of photoacid generators using a photolithography machine
[0086] Among them, the structural formula of PAG-6-1 is: , the structural formula of PAG-6-2 is: , the structural formula of PAG-6-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; the exposure energy data of the corresponding formulas of PAG-6-1, PAG-6-2, and PAG-6-3 are 21mj, 29mj, and 36mj, respectively. The stronger the acidity of the photoacid, the less light is required, and only the photoacid structure is consistent in the formula, and the chromophore of the photoacid generator is inconsistent, which means that the relative size of the acid generation efficiency of the photoacid generator at the same light wavelength (248nm) is: PAG-6-1>PAG-6-2>PAG-6-3.
[0087] Example 7 This embodiment provides a method for testing the relative size of the acid generation efficiency of a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 7: Table 7 Relative size of photoresist formulas for testing the acid generation efficiency of photoacid generators using a photolithography machine
[0088] Among them, the structural formula of PAG-7-1 is: , the structural formula of PAG-7-2 is: , the structural formula of PAG-7-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; The exposure energy data of the corresponding formulas of PAG-7-1, PAG-7-2, and PAG-7-3 are 17mj, 25mj, and 31mj, respectively. The stronger the acidity of the photoacid, the less light is needed, and only the photoacid structure is consistent in the formula, and the chromophores of the photoacid generator are inconsistent, indicating that the relative size of the acid generation efficiency of the photoacid generator at the same light wavelength (248nm) is: PAG-7-1>PAG-7-2>PAG-7-3. The difference between this embodiment and embodiment 6 is that the components of the photoresist formula are adjusted, but the acid generation efficiency results of the photoacid generator obtained are consistent, which can once again prove that the testing method of the present invention is practical and effective.
[0089] Example 8 This embodiment provides a method for testing the relative size of the acid generation efficiency of a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 8: Table 8 Relative size of photoresist formulas for testing the acid generation efficiency of photoacid generators using a photolithography machine
[0090] Among them, the structural formula of PAG-8-1 is: , the structural formula of PAG-8-2 is: , the structural formula of PAG-8-3 is: ; Step 2, perform a photolithography test on the photoresist sample using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 90℃90s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 90℃60s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; the exposure energy data of the corresponding formulas of PAG-8-1, PAG-8-2, and PAG-8-3 are 30mj, 24mj, and 20mj, respectively. The stronger the acidity of the photoacid, the less light is required, and only the photoacid structure is consistent in the formula, and the chromophore of the photoacid generator is inconsistent, which means that the relative size of the acid generation efficiency of the photoacid generator at the same light wavelength (248nm) is: PAG-8-3>PAG-8-2>PAG-8-1.
[0091] Example 9 This embodiment provides a method for testing the relative size of the acid generation efficiency of a photoacid generator using a photolithography machine, comprising the following steps: Step 1, prepare a photoresist sample according to a photoresist formula; the photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; the photoresist formula in this embodiment is shown in Table 9: Table 9 Relative size of photoresist formulas for testing the acid generation efficiency of photoacid generators using a photolithography machine
[0092] Among them, the structural formula of PAG-9-1 is: , the structural formula of PAG-9-2 is: , the structural formula of PAG-9-3 is: ; Step 2, the photoresist sample is subjected to a photolithography test using a photolithography machine according to the photolithography process to obtain exposure energy data (Eop data) of the photoresist sample; the equipment used in the photolithography process includes: a coating developer, a photolithography machine, and a FEB length measuring instrument, specifically: coating developer: LITHIUS Pro Z; photolithography machine: ASML TWINSCAN 860; FEB length measuring instrument: CD-SEM CG6300; the conditions of the photolithography process are: HMDS: On; PAB: 120℃60s; Thickness: 1800Å; TARC: AQ8A, 430Å, 90℃60s; Illumination mode: Annular, NA 0.78, σout=0.7, σin=0.3; PEB: 135℃90s; DEV: single puddle 15s; Anchor Point: S140nmP280; finally, the exposure energy data (Eop data) of the three groups of recipe samples in this embodiment are obtained; Step 3, according to the exposure energy data, obtain the acid intensity of the photoacid generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; the exposure energy data (Eop data) of the corresponding formulas of PAG-9-1, PAG-9-2, and PAG-9-3 are 51mj, 33mj, and 22mj, respectively. The stronger the acidity of the photoacid, the less light is required, and only the photoacid structure is consistent in the formula, and the chromophores of the photoacid generator are inconsistent, which means that the relative size of the acid generation efficiency of the photoacid generator at the same light wavelength (248nm) is: PAG-9-3>PAG-9-2>PAG-9-1.
[0093] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for testing acid strength and acid production efficiency using a photolithography machine, characterized in that: The steps include: Step 1, preparing a photoresist sample according to a photoresist recipe; The photoresist formula includes a photoacid generator, a quencher, a resin, a leveling agent, and a solvent; Step 2, performing a photolithography test on the photoresist sample using a photolithography machine according to a photolithography process to obtain exposure energy data of the photoresist sample; Step 3, according to the exposure energy data, obtaining the relative magnitude of the photoacidity intensity generated by the selected photoacid generator and the acid generation efficiency of the photoacid generator; Wherein, when the chromophores of the photoacid generator are consistent, the acid intensity of the photoacid generated by the photoacid generator increases as the exposure energy data decreases; When the chromophores of the photoacid generator are not consistent and the photoacid generated is the same, the acid generation efficiency of the photoacid generator increases as the exposure energy data decreases.
2. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: The photoacid generator in step 1 includes one of a sulfonium salt ionic photoacid generator, an iodonium salt ionic photoacid generator, a sulfonyldiazomethane molecular photoacid generator, a sulfonyloxyimide molecular photoacid generator, a polyphenol sulfonate molecular photoacid generator, a nitrobenzyl sulfonate molecular photoacid generator, a glyoxime molecular photoacid generator, and a di-(trichloromethane)-triazine molecular photoacid generator.
3. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: The quencher in step 1 includes one or more of pyridine compounds, tertiary alkylamines, alicyclic amines, trialkanol tertiary amines, tetraalkylammonium hydroxides, and vinylpyridine polymers.
4. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: The resin in step 1 is a copolymer or a homopolymer, with a molecular weight Mw of 3000-100,000 and a molecular weight distribution index PDI value of 1.02-3.
5. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: The leveling agent is a surfactant.
6. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 5, characterized in that: The surfactant contains a silicon surfactant or a fluorine surfactant.
7. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: The solvent in step 1 is one or more of a carboxylic acid ester solvent, a ketone solvent, an ether solvent, and a cyclic amide solvent.
8. The method for testing acid strength and acid generation efficiency using a photolithography machine according to claim 1, characterized in that: In terms of weight percentage, the proportion of each component in the photoresist formula is as follows: photoacid generator: 0.001-0.3%; Quencher: 0.01-0.5%; Resin: 1-50%; Leveling agent: 0.002%; Solvent: 50-90%.
9. An application of the method for testing acid strength and acid generation efficiency using a photolithography machine according to any one of claims 1 to 8, characterized in that: The method is used to test the relative strength of the photoacid generated by the photoacid generator and the acid generation efficiency of the photoacid generator.
10. A database, characterized in that: The database includes test results after testing using the method for testing acid strength and acid generation efficiency using a photolithography machine as described in any one of claims 1-8.